Zero-Sum Construal of Workplace Success Promotes Initial Work Role Behavior by Activating Prevention Focus: Evidence From Chinese College and University Graduates - Zhang, Haiyan; Sun, Shuwei (Frontiers in Psychology, 2020)
Given that the population of Chinese college & university graduates has become larger and larger year by year since 1999, the problem of individual graduate’s employment and workplace adaptability has captured widespread social concern and been interested by both scholars and practitioners. Initial work role behavior is essential to individual graduate’s successful workplace adaptability and sustainable career development as a new employee. Based on social cognition theory, sense-making theory, and regulatory focus theory, we argue that individual graduate’s zero-sum construal of workplace success is a key factor influencing his or her initial workplace adaptability, which not only directly promotes initial work role behavior but also elicits the new employee’s prevention focus inclination which in turn enhances initial work role behavior in the context of China’s present steady economic development. Moreover, individual graduate’s average pay level moderates the mediating effect of prevention focus, such that the higher the average pay level is, the stronger the positive effect of zero-sum construal on initial work role behavior via prevention focus becomes. Two-stage survey data from 258 Chinese university graduates who have already entered organizations as full-time employees and their direct supervisors provided evidence consistent with our hypothesized first-stage moderated mediation model. Implications, limitations, and future research suggestions are discussed as well.